2016
DOI: 10.1016/j.amsu.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Detection of benign hilar bile duct stenoses - A retrospective analysis in 250 patients with suspicion of Klatskin tumour

Abstract: IntroductionThe aim of this study was to identify clinical, laboratory and radiological parameters to distinguish benign from malignant stenoses of the proximal bile duct.MethodsBetween 1997 and 2011, 250 patients were referred to our clinic with hilar bile duct stenoses suspicious for Klatskin tumour. Medical histories, clinical data, pre-interventional laboratory tests, imaging findings, as well as therapeutic approach and patient outcome were compared to final histological results. All data were retrieved f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Surgical resection of pCCA is guided by the Bismuth-Corlette classification (30) with types II-IV requiring extensive surgery which involves major hepatic resection in the form of extended hepatectomy and caudate lobectomy (Figure 1) (29,31). Reports of up to 25% of patients who underwent surgical resection for suspected CCA and subsequently found to have benign disease, highlight an urgent need for more accurate diagnostics (32)(33)(34). A diagnostic modality with improved sensitivity over standard cytology and histology, may therefore prevent unnecessary extensive surgery which has been linked with morbidity and mortality rates as high as 60% and 18%, respectively (29,35).…”
Section: Diagnosis and Management Of Benign And Malignant Biliary Stricturesmentioning
confidence: 99%
“…Surgical resection of pCCA is guided by the Bismuth-Corlette classification (30) with types II-IV requiring extensive surgery which involves major hepatic resection in the form of extended hepatectomy and caudate lobectomy (Figure 1) (29,31). Reports of up to 25% of patients who underwent surgical resection for suspected CCA and subsequently found to have benign disease, highlight an urgent need for more accurate diagnostics (32)(33)(34). A diagnostic modality with improved sensitivity over standard cytology and histology, may therefore prevent unnecessary extensive surgery which has been linked with morbidity and mortality rates as high as 60% and 18%, respectively (29,35).…”
Section: Diagnosis and Management Of Benign And Malignant Biliary Stricturesmentioning
confidence: 99%
“…Because of the diagnostic difficulties sometimes encountered, definitive treatment such as surgery or chemotherapy may be delayed or given incorrectly, with potential consequences for patients. In one study of 238 patients undergoing surgical resection of suspected cholangiocarcinoma, 13% were found to have benign disease (1). Many of these patients have an autoimmune cholangiopathy (including IgG4-related disease) which can be effectively treated with steroids and other immunosuppressives.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found 13.6% of patients undergoing surgical resection for a suspected Klatskin tumour had benign disease. 2 Such major surgery is associated with appreciable morbidity and not insignificant morbidity. Therefore, confirming the diagnosis before surgery is preferable.…”
Section: Introductionmentioning
confidence: 99%